Logistic equations in tumour growth modelling - Foryś, Urszula; Marciniak-Czochra, Anna (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to present some approaches to tumour growth modelling using the logistic equation. As the first approach the well-known ordinary differential equation is used to model the EAT in mice. For the same kind of tumour, a logistic equation with time delay is also used.
Keywords: logistic equation; delay differential equations; reaction-diffusion equation; stability; global stability; Hopf bifurcation; spatial pattern; Ehrlich ascities tumour